2018
DOI: 10.1007/s10549-018-4789-8
|View full text |Cite
|
Sign up to set email alerts
|

Physician peer group characteristics and timeliness of breast cancer surgery

Abstract: The likelihood of surgical delay varied substantially across physician peer groups and was associated with provider density and patient racial composition.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 26 publications
0
9
0
Order By: Relevance
“…Research has shown that hypofractionated whole-breast irradiation (HF-WBI) is as effective as conventionally fractionated whole-breast irradiation (CF-WBI) in reducing the risk of recurrence and mortality following breast conserving surgery in patients with early-stage breast cancer. 1,2 Compared to CF-WBI, which typically involves 25-33 radiation treatments, HF-WBI uses a higher radiation dose per fraction but requires fewer (approximately [15][16][17][18][19][20] treatments. Hence, HF-WBI is less expensive and more convenient than CF-WBI, 3 and yields improved patient quality of life (eg, improved cosmetic outcome, less toxic effects, and less fatigue).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Research has shown that hypofractionated whole-breast irradiation (HF-WBI) is as effective as conventionally fractionated whole-breast irradiation (CF-WBI) in reducing the risk of recurrence and mortality following breast conserving surgery in patients with early-stage breast cancer. 1,2 Compared to CF-WBI, which typically involves 25-33 radiation treatments, HF-WBI uses a higher radiation dose per fraction but requires fewer (approximately [15][16][17][18][19][20] treatments. Hence, HF-WBI is less expensive and more convenient than CF-WBI, 3 and yields improved patient quality of life (eg, improved cosmetic outcome, less toxic effects, and less fatigue).…”
Section: Introductionmentioning
confidence: 99%
“…13,14 Several studies have shown that physicians' use of cancer care therapies is influenced by "peer groups" (groups of physicians who frequently share patients with one another). 13,15,16 There is also evidence for large variation in clinical practice across physician peer groups, 13,17 suggesting possible distinct practice styles. For instance, use of magnetic resonance imaging before breast cancer surgery varied from 0% to 81% across physician peer groups.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“… 1 Disparities in time to treatment are well documented, with AA women facing a longer time to treatment than white women for surgery, chemotherapy, radiation, and endocrine therapy. 2 5 Because delays in treatment correlate with worse outcomes and reduced overall survival, it is imperative to address this inequity. 5 …”
mentioning
confidence: 99%
“…1 Disparities in time to treatment are well documented, with AA women facing a longer time to treatment than white women for surgery, chemotherapy, radiation, and endocrine therapy. [2][3][4][5] Because delays in treatment correlate with worse outcomes and reduced overall survival, it is imperative to address this inequity. 5 Song et al 6 conducted a retrospective review of the National Cancer Database (NCDB), identifying 557,816 women older than 65 years with non-metastatic breast cancer (2010)(2011)(2012)(2013)(2014)(2015)(2016)(2017).…”
mentioning
confidence: 99%